自国開催の国際大会における実力不発揮の心理的プロセスの検討 - 米丸, 健太; 福井, 邦宗; 奥野, 真由; 鈴木, 敦; 佐々木, 丈予; 立谷, 泰久 (Sports Science in Elite Athlete Support, 2018)
The purpose of this study was to investigate the psychological process of Japanese athletes who were not reaching best performance in international competition held in Japan. Participants were 3 athletes (2 male and 1 female) who had participated in international competitions held in Japan and other countries and not able to perform their best in their own country. We conducted a group interview with them lasting about two hours. Verbatim data were analyzed using the Modified Grounded Theory Approach (M-GTA), and the following psychological process was confirmed. The participants felt an “upsurge of their own country” that was increased by the people they cared about, supporters, and the media, which became stressors. They made them feel “social responsibility” and a “sense of duty” and strengthened “inability.” They fell into a “negative spiral” such that they could not cope flexibly and find solutions to their problems. In this situation, they constrained external events such as others and instruments and entered the vague situation of not finding a solution. They felt anxiety and strong pressure, which led to their suboptimal performance. The results suggested that coping with problems flexibly and concentrating on something they should do prevent not to reach one’s best performance. Future research is needed that carefully considers the relation between concept or category and personality traits. As research results accumulate, psychological support will improve.